2016
DOI: 10.30789/rcneumologia.v28.n2.2016.217
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia de patologías relacionadas con el asbesto crisotilo en trabajadores de una empresa de productos de crisotilo-cemento

Abstract: Introducción: en Manizales opera una fábrica de productos de fibrocemento que emplea, desde el inicio de sus operaciones, fibras de asbesto crisotilo bajo condiciones de higiene industrial controladas.Objetivo: estudiar la prevalencia de las patologías relacionadas con la exposición a las fibras de crisotilo en el aire en la totalidad de la población activa al 31 de diciembre de 2012, la historia de exposición acumulada a fibras, la antigüedad en la empresa y la historia de tabaquismo.Materiales y métodos: est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…There is little about asbestos disease in the scientific literature from Colombia. One flawed study of Colombian asbestos-exposed workers [10] reported no disease in an asbestos cement plant. The average latency was short, about twelve years, and only X-rays with an ILO reading of 1/1 or higher were considered possibly positive, although the ILO guidelines themselves clearly note that films read as 1/0 or higher are to be considered abnormal.…”
Section: Introductionmentioning
confidence: 99%
“…There is little about asbestos disease in the scientific literature from Colombia. One flawed study of Colombian asbestos-exposed workers [10] reported no disease in an asbestos cement plant. The average latency was short, about twelve years, and only X-rays with an ILO reading of 1/1 or higher were considered possibly positive, although the ILO guidelines themselves clearly note that films read as 1/0 or higher are to be considered abnormal.…”
Section: Introductionmentioning
confidence: 99%